Lung scanning in carcinoma of the bronchus. Issue 1 (January 1971) - Walker, R. H. Secker; Provan, J. L.; Jackson, J. A.; Goodwin, J.
Abstract : The lung scans of 101 patients with carcinoma of the bronchus have been compared with the bronchoscopic and radiographic findings. As the tumour approaches the hilum as judged by bronchoscopy or the chest radiograph the relative perfusion of the affected lung decreases. When the relative perfusion of the affected lung is less than one third of the total the tumour is likely to be inoperable. The reduction in perfusion is related to involvement of the vessels in the hilum by tumour and to a lesser extent to bronchial obstruction. Defects in perfusion in the unaffected lung were seen in 53 patients and were usually due to chronic bronchitis and emphysema or inactive pulmonary tuberculosis. In the management of patients with carcinoma of the bronchus lung scans are of value in predicting when a tumour is likely to be inoperable and also in giving an indication as to whether a pneumonectomy or lobectomy will be possible. In addition, defects in the contralateral lung may be sufficiently large to contraindicate surgery.